Correction: Beyond catalysis and membranes: visualizing and solving the challenge of electrode water accumulation and flooding in AEMFCs. Issue 4 (9th March 2018) - Omasta, Travis J.; Park, Andrew M.; LaManna, Jacob M.; Zhang, Yufeng; Peng, Xiong; Wang, Lianqin; Jacobson, David L.; Varcoe, John R.; Hussey, Daniel S.; Pivovar, Bryan S.; Mustain, William E.
Abstract : Correction for 'Beyond catalysis and membranes: visualizing and solving the challenge of electrode water accumulation and flooding in AEMFCs' by Travis J. Omasta et al., Energy Environ. Sci., 2018, DOI: ;10.1039/c8ee00122g .